Resistance to the dehumanisation of asylum seekers in Australia's mediated public sphere: an audience perspective. (September 2020) - Haw, Ashleigh; Fozdar, Farida; Cover, Rob
Media narratives that dehumanise asylum seekers have tremendous power to shape and reinforce public support for policies that jeopardise the well-being of some of the world's most vulnerable people. Research suggests that such dehumanisation is exacerbated by the limited opportunities these groups have to contribute to media coverage about their experiences. In response, scholars have advocated for more inclusion of asylum seekers' voices in news coverage; however, little is known about how Australian media audiences are engaging with this issue. This article discusses research utilising Critical Discourse Analysis alongside a cultural studies Audience Reception framework to examine the perspectives of 24 Western Australians concerning news discourses about asylum seekers. Resistance to dehumanising constructions was a recurring theme, with many participants arguing for greater inclusion of asylum seekers voices' in news depictions of their plight. These findings suggest that some audiences are challenging and resisting dehumanising discourses about asylum seekers and in some cases, demonstrating awareness of Australian media's evident exclusion of their voices. Examined through Judith Butler's social ethics lens, we consider these findings in the light of positions that advocate for the provision of voice as a means to a more ethical and inclusive Australian media.